1995
DOI: 10.1111/j.1432-1033.1995.849_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poliovirus 2Apro on Vaccinia Virus Gene Expression

Abstract: The effects of transient expression of poliovirus 2Ap"' ori 11220 cleavage in COS cclls h:tve bccn analyzed. When 2AP"' was cloned in plasmid pTMl and transiently expressed in COS cclls, efficient cleavage of p220 occurred after infection of thesc cells with ii rccombinant vaccinia virus hearing phage T7 R N A polymerase. High numbers of COS cells were transfectcd with pTMf-2A, as ,judged hy 11220 cleavage, thereby allowing an analysis of the effects of poliovirus 2AI"" on vaccinia virus gene expression. A 40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…By contrast, vaccinia virus replication was powerfully inhibited in 2A7d-On cells, in good agreement with the result showing that poliovirus 2A pro interferes with vaccinia virus translation (19). Although picornavirus translation in 2A7d cells was allowed, there was no stimulation of the total amount of viral protein synthesized, resulting in levels of virus production similar to those in 2A7d-Off cells.…”
Section: Asupporting
confidence: 77%
See 3 more Smart Citations
“…By contrast, vaccinia virus replication was powerfully inhibited in 2A7d-On cells, in good agreement with the result showing that poliovirus 2A pro interferes with vaccinia virus translation (19). Although picornavirus translation in 2A7d cells was allowed, there was no stimulation of the total amount of viral protein synthesized, resulting in levels of virus production similar to those in 2A7d-Off cells.…”
Section: Asupporting
confidence: 77%
“…Immunoblotting was carried out as described previously (6). The anti-2C (55), -2A and -3C (8), -eIF4GI (19), and -eIF4GII (23) sera were obtained and used as described previously. The anti-eIF4FG-2 antiserum was a generous gift from N. Sonenberg (McGill University).…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further work analyzing the action of this protease on vaccinia virus gene expression indicated that 2A pro profoundly interferes with vaccinia virus replication, such that no viral protein synthesis is detected at late times of infection (48). Therefore, the action of the different 2A…”
Section: Inhibition Of Vaccinia Virus Translation By Several Poliovirmentioning
confidence: 99%